2010
DOI: 10.1016/j.jsbmb.2009.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen utilization of IGF-1-R and EGF-R to signal in breast cancer cells

Abstract: As breast cancer cells develop secondary resistance to estrogen deprivation therapy, they increase their utilization of non-genomic signaling pathways. Our prior work demonstrated that estradiol causes an association of ERα with Shc, Src and the IGF-1-R. In cells developing resistance to estrogen deprivation (surrogate for aromatase inhibition) and to the anti-estrogens tamoxifen, 4-OHtamoxifen, and fulvestrant, an increased association of ERα with c-Src and the EGF-R occurs. At the same time, there is a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 32 publications
2
61
0
1
Order By: Relevance
“…Interaction of IGF1R and ER has been shown in numerous studies, but this interaction also involves physical co-localization. Reported co-localization of the ER, which is generally localized in the nucleus, with IGF1R at the cell membrane underscores the diversity of receptor localization [35]. Taken together, these data suggest that protein localization of tyrosine kinase receptors is a highly dynamic biological process.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Interaction of IGF1R and ER has been shown in numerous studies, but this interaction also involves physical co-localization. Reported co-localization of the ER, which is generally localized in the nucleus, with IGF1R at the cell membrane underscores the diversity of receptor localization [35]. Taken together, these data suggest that protein localization of tyrosine kinase receptors is a highly dynamic biological process.…”
Section: Discussionmentioning
confidence: 69%
“…Confocal microscopy images studying subcellular localization of IGF1R show cytoplasmic staining [35,36]. Some have reported cytoplasmic IGF1R staining by IHC [37,38], while others have chosen to ignore cytoplasmic staining, although endoplasmatic staining had been present [39].…”
Section: Discussionmentioning
confidence: 99%
“…Other potentially critical factors that may be relevant in TNBC include the interplay between EGFR and insulin-like growth factor receptor signaling systems and production of cell surface effectors such as the subclass of heparin sulfate proteoglycans known as syndecans (52)(53)(54)(55)(56). Understanding how these different factors are integrated to drive metastatic progression will provide the Somewhat surprisingly, our data also appear to exclude a role for autocrine IL-6 because EMT programs fail to diminish the ability of NME cells to activate STAT3 in response to exogenous IL-6.…”
Section: Figure 4 Emt Inhibits Egfr-dependent Stat3 Signalingmentioning
confidence: 99%
“…For example, IGF-2 is recognized by IGF-1R and activates both estrogen receptor-alpha and estrogen receptor-beta (Richardson et al, 2011). Additionally, Song et al (2010) demonstrated that estrogen can utilize either the IGF-1R or the estrogen receptor (Song et al, 2010). These underlying mechanisms, especially their link to estrogen, may help us better understand the controversy of premenopausal obesity-related breast cancer.…”
Section: Obesitymentioning
confidence: 99%